Iowa Birdline update, March 11, 1991 notes - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1991)
Notes for the Iowa Birdline update for March 11, 1991. Highlights include a Cinnamon Teal and a Lesser Black-backed Gull. Waterfowl migration is peaking for diving ducks and geese. Epson - sheet feed/flatbed